"What's love got to do with it?" Bringing love into international development research. Issue 3 (3rd July 2022) - Cameron, John
ABSTRACT: This article argues that international development research needs to focus more attention on love, for two reasons. First, to better understand the emotional experiences of poverty, injustice and development, and second, to understand the ways that public policy can shape the capabilities for love. Following analysis of the importance of love for physical and mental health, the article examines areas of public policy in the global North and South that may undermine the capability to love and be loved. The article concludes by highlighting the ways that attention to love may help to humanize international development research and overcome "othering."